Application of Graphene and its Derivatives in Detecting Hazardous Substances in Food: A Comprehensive Review - Pei, Jinjin; Ren, Ting; Huang, Yigang; Chen, Rui; Jin, Wengang; Shang, Shufeng; Wang, Jinze; Liu, Zhe; Liang, Yinku; Abd El-Aty, A. M. (Frontiers in Chemistry, 2022)
Graphene and its derivatives have been a burning issue in the last 10 years. Although many reviews described its application in electrochemical detection, few were focused on food detection. Herein, we reviewed the recent progress in applying graphene and composite materials in food detection during the past 10 years. We pay attention to food coloring materials, pesticides, antibiotics, heavy metal ion residues, and other common hazards. The advantages of graphene composites in electrochemical detection are described in detail. The differences between electrochemical detection involving graphene and traditional inherent food detection are analyzed and compared in depth. The results proved that electrochemical food detection based on graphene composites is more beneficial. The current defects and deficiencies in graphene composite modified electrode development are discussed, and the application prospects and direction of graphene in future food detection are forecasted.